2006
DOI: 10.1088/0953-8984/18/25/s05
|View full text |Cite
|
Sign up to set email alerts
|

Nonhydrostatic compression of gold powder to 60 GPa in a diamond anvil cell: estimation of compressive strength from x-ray diffraction data

Abstract: Two gold powder samples, one with average crystallite size of ≈30 nm (n-Au) and another with ≈120 nm (c-Au), were compressed under nonhydrostatic conditions in a diamond anvil cell to different pressures up to ≈60 GPa and the x-ray diffraction patterns recorded. The difference between the axial and radial stress components (a measure of the compressive strength) was estimated from the shifts of the diffraction lines. The maximum micro-stress in the crystallites (another measure of the compressive strength) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
34
1

Year Published

2010
2010
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 53 publications
8
34
1
Order By: Relevance
“…The agreement between the strength derived from the linewidth using the above equation and that obtained from the line-shift analysis of the radial diffraction data in many cases [13,27,30,31] provided support for Eqs. (1) and (2).…”
Section: Discussionsupporting
confidence: 57%
“…The agreement between the strength derived from the linewidth using the above equation and that obtained from the line-shift analysis of the radial diffraction data in many cases [13,27,30,31] provided support for Eqs. (1) and (2).…”
Section: Discussionsupporting
confidence: 57%
“…The diffraction-line broadening has been used to determine the maximum stress in the stress distribution in the crystallites. [2][3][4][5][6][7][8][9][10][11][12] The maximum stress p max (ffi eY, where e and Y are the micro-strain and the aggregate Young's modulus, respectively) is often termed the micro-differential stress (micro-DS) and is taken as the measure of compressive strength of the polycrystalline sample material. Some studies used p max (e.g., Refs.…”
Section: Introductionmentioning
confidence: 99%
“…2 and 5-7), whereas others 2p max (e.g., Refs. [8][9][10][11][12] as the measure of micro-DS. The macro-stresses at the center of the sample compressed in a DAC possess a cylindrical symmetry about the load axis, the axial stress component r 33 being larger than the radial stress component r 11 .…”
Section: Introductionmentioning
confidence: 99%
“…The values of C ij (0) and C 0 ij ð0Þ for silver were taken from the measurements by Daniels and Smith [25]. The earlier studies have shown that 2p max is a measure of compressive strength in agreement with the strength derived from the shifts of the diffraction lines [11,14].…”
Section: Methods Of Data Analysismentioning
confidence: 86%
“…The micro-stresses vary randomly in direction and magnitude in each crystallite [3], and produce micro-strains that cause the diffraction lines to broaden. The product of micro-strain and an appropriate Young's modulus is a measure of the compressive yield strength of the solid sample [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. It may be mentioned that the X-ray diffraction measures lattice strains that are elastic even though the sample undergoes considerable plastic deformation during pressurization.…”
Section: Introductionmentioning
confidence: 99%